Evaluasi Pelayanan Swamedikasi di Apotek Sehat Farma Banjarharjo - Ifani Maesarah; Hanari Fajarini; Erin Nursanti (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Self-medication is a form of pharmaceutical service that allows the public to treat mild symptoms independently without a doctor’s prescription. While beneficial, improper self-medication practices can pose health risks such as drug resistance and misuse of prescription-only medicines. If not carried out carefully, it may lead to further issues such as bacterial resistance and dependency. This study aims to evaluate the self-medication services at Sehat Farma Pharmacy in Banjarharjo. A descriptive method was employed using interviews and direct observations to provide a comprehensive overview of self-medication practices in the field. Informants included a pharmacist, pharmaceutical vocational staff, and patients engaged in self-medication. The results indicate inconsistencies in the service flow, including the provision of prescription-only medications without proper medical consultation. There is a need to improve the understanding and adherence to appropriate service standards to enhance the safety and effectiveness of self-medication practices.